Peer Assessment as a Tool for Measuring Employee Affective Commitment - Dini Riani; Veri Aryanto Sopiansah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the role of peer assessment in identifying employee affective commitment within Bandung City government agencies. Affective commitment, encompassing emotional attachment, identification, and involvement, is influenced by work experience, personal values, and social support. Grounded in Social Network Theory, which highlights the significance of social interactions in workplace networks, this research employs a quantitative descriptive approach. Data was collected via questionnaires from employees with at least one year of service, assessing three commitment dimensions through peer evaluations to ensure objectivity. Findings reveal a high level of affective commitment, with emotional engagement as the primary contributor and participation the lowest. Positive peer perceptions significantly enhance employees’ sense of belonging and loyalty, validating peer assessment as an effective alternative indicator of affective commitment. These results align with Organizational Support and Social Network Theories, emphasizing the role of social relationships in fostering emotional bonds. The study offers practical insights for developing socially driven internal evaluation systems to boost employee loyalty and performance. Despite its contributions, limitations include potential peer assessment biases and context-specific findings, suggesting future research to explore causal relationships and broader applications.